Analisis Penerapan Sistem Informasi Akuntansi Persediaan Obat-Obatan Pada Perusahaan Farmasi Di Surabaya (Studi Kasus Pt. Sakajaja Makmur Abadi) - Novenia Dwi Nofa; J.B. Amiranto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to determine how the inventory accounting information system for pharmaceutical companies. This research was conducted at PT. Sakajaja Makmur Abadi which is a pharmaceutical company that has thousands of drug supplies and different types of uses. This research is a qualitative descriptive study. The data source used is primary data in the form of interviews and secondary data in the form of documentation. The results of this study indicate that PT. Sakajaja Makmur Abadi has implemented an inventory accounting information system correctly and properly in accordance with the provisions regulated by the Food and Drug Supervisory Agency (BPOM). Inventory system at PT. Sakajaja Makmur Abadi is based on well-computerized technology. However, weaknesses were still found in the existing inventory accounting information system, namely the lack of compliance with procedures that should be carried out and also the lack of competence of existing human resources.